(untitled) - Economy and environment program for Southeast Asia (EEPSEA) (Phillippines, 2016)
This is repost introduce about environmental cost of water pollution, valuing ecosystem services, regulatory measures for pollution control.
Keywords: Nước,Water; Ô nhiễm,Chi phí,Pollution,Costs